Plant-Soil Interactions - Faucon, Michel-Pierre (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Plant-soil interactions play an important role in the functioning of ecosystems. This book presents recent research advances on the effects of soil factors on plant communities and the role of ecological complementarity and species diversity in soil properties and ecosystem services. It addresses cultivated, degraded and natural soils, in fields as well as in greenhouse experiments, at different latitudes. It may be found useful by researchers, students and practitioners.